2009
DOI: 10.1007/s00217-009-1069-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decontamination on the microbial load, the sensory quality and the nutrient retention of ready-to-eat white cabbage

Abstract: The effect of different decontamination treatments such as washing with sodium hypochlorite (20 and 200 mg/L), peroxyacetic acid (80 and 250 mg/L), neutral electrolysed oxidising water (4.9 and 31.7 mg/L free chlorine) and contact with 1.55 mg/L chlorine dioxide gas on the microbial and sensory quality, and the nutrient content of fresh-cut white cabbage was studied. Only rinsing with 200 mg/L sodium hypochlorite, peroxyacetic acid or contact with gaseous chlorine dioxide resulted in significantly higher reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…These results are in accordance with those found in raw cabbage (Peñas, Frias, Gómez, & Vidal-Valverde, 2010) and other Brassica fresh vegetables (Feng-Di, Bao-Ping, Bo, & Bei-Zhong, 2007;Olarte, Sanz, Echávarri, & Ayala, 2009;Vandekinderen et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with those found in raw cabbage (Peñas, Frias, Gómez, & Vidal-Valverde, 2010) and other Brassica fresh vegetables (Feng-Di, Bao-Ping, Bo, & Bei-Zhong, 2007;Olarte, Sanz, Echávarri, & Ayala, 2009;Vandekinderen et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Quality Information Service on the Total Profit of the Food Supply Chain. According to (13), (17), (18), (21), (23), (25), (26), (27), and (37), we use 2 = 6, 1 ∈ [0, 10], and then we use Matlab software to graph the results (see Figure 7). We analyze the impact of the level of the online channel's food quality information service on the profit of the food supply chain as follows.…”
Section: The Impact Of the Level Of The Online Channel's Foodmentioning
confidence: 99%
“…The prices in the online and offline channels under the Stackelberg game are 1 , 2 , respectively; see (17) and (18), and taking 1 , 2 into (1), we can obtain the demand of the online and offline channels under the Stackelberg game, 1 , 2 , respectively. Finally, we insert the parameter values into (25) and find that the food processing factory's profit before coordination is 18354.…”
Section: The Impact Of the Quantity Discount Mechanism On Thementioning
confidence: 99%
See 1 more Smart Citation
“…Contaminated pork with Salmonella Typhi showed reduction counts by 0.47 and 0.3 log CFU/g when NEW and NaClO treatments were used however, no significant difference was detected when results were compared with SS treatment. It has been reported that treatments combined with shaking methodologies improve the sanitization process 12,[35][36][37] ; this could remove surface bacteria and allow NEW to come into contact with deeper cells. Treated pork chops were kept at 4 °C for 8 days.…”
Section: Resultsmentioning
confidence: 99%